In vitro test systems supporting the development of improved pest control methods: a case study with chemical mixtures and bivalve biofoulers - Silva, Carlos (2022)
Using the bivalve macrofouler Corbicula fluminea, the suitability of in vitro testing as a stepping stone towards the improvement of control methods based on chemical mixtures was addressed in this study. In vitro cholinesterase (ChE) activity inhibition following single exposure of C. fluminea tissue to four model chemicals (the organophosphates dimethoate and dichlorvos, copper and sodium dodecyl phosphate [SDS]) was first assessed. Consequently, mixtures of dimethoate with copper and dichlorvos with SDS were tested and modelled; mixtures with ChE revealed synergistic interactions for both chemical pairs. These synergic combinations were subsequently validated in vivo and the increased control potential of these selected combinations was verified, with gains of up to 50% in C. fluminea mortality relative to corresponding single chemical treatments. Such consistency supports the suitability of using time- and cost-effective surrogate testing platforms to assist the development of biofouling control strategies incorporating mixtures.